Arthroscopic microfracture alone or combined application of acellular scaffold: Which one is more effective in the treatment of osteochondral lesions of the talus? - Cengiz, Bertan; Moradi, Ramin (Journal of Surgery and Medicine, 2021)
Background/Aim: The optimal treatment method of the talar osteochondral lesions (TOLs) is still controversial. Although the success of arthroscopic microfracture treatment (AMFx) in smaller lesions is known, different treatment methods are tried in larger-sized TOLs. This study aimed to compare the clinical and radiological outcomes of the single-step AMFx repair procedure and the combined application of AMFx and cell-free scaffold (CFS) in the treatment of TOLs. Methods: This retrospective cohort study included patients presenting with a TOL larger than 1.5 cm2 and smaller than 3 cm2 between March 2015 and June 2018 who received arthroscopic treatment and attended follow-up for at least 24 months. Eighteen patients (group 1) were treated with the AMFx method, and 16 patients (group 2) with AMFx + CFS. American Orthopedic Foot and Ankle Society (AOFAS), Visual Analog Scale (VAS), and Tegner Activity Scores were used for clinical evaluation, and MOCART (magnetic resonance observation of cartilage repair tissue) score was used to assess cartilage repair tissue. Results: The mean patient age was 33.47 (8.67) years and the mean follow-up time was 32.24 (9.33) months. There was no significant difference between the two groups in terms of age (P=0.984), body mass index (P=0.450), defect size (P=0.081) and follow-up time (P=0.484). The median AOFAS score increased from preoperative assessment until follow-up assessment at 12 months in groups 1 (P<0.001) and group 2 (P<0.001). There was no significant difference between the two groups in terms of clinical scores, or the components of the MOCART score. Conclusion: Comparisons revealed that outcomes at the end of 24-month follow-up were similar between two groups. Therefore, TOLs appear to benefit similarly from the AMFx and AMFx + CFS techniques.